The effects of facial cooling on physiological and perceptual responses during a simulated Épée fencing competition: a pilot study - Morris, G. B.; Glaister, M. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: The aim of this study was to investigate the effects of facial cooling on physiological and perceptual responses during a simulated fencing competition.